Bahasa dan Akal Dalam Ijtihad Mazhab Hanafi - Teguh Prawiro (STIT Muslim Asia Afrika, 2022)
The emergence of various schools of thought in Islamic law cannot be separated from the problems of language and reason in every legal consideration in ijtihad. The polarization of madrasah ahl hadith which tend to maintain textually the use of naqli propositions and madrasah ahli ra’yi which use more logical reasoning in contextually understanding of Alquran and Sunah is also not free from language and reason problems. The first group which referring of thoughts that do not provide adequate portion of the existence of reason in ijtihad. While the second group is considered as a group that gives a wide enough role of reason in ijtihad. For them sharia always have a basis and goals to be realized in human life. The Hanafi school places reason as a source of law after the Qur'an and Sunah. Reason plays a role as a complement to revelation. Therefore reason cannot conflict with the will of revelation. Thus, if in madrasah ahli ra'yi rationality becomes the basic foundation of Islamic legal thought, then the Hanafi school has quite significant relevance to the building of this concept.